Strategi Penjualan Produk UKM Berbasis Lorong - Sewang Sewang; A. Nur Asri Ainun (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The sales strategy of SME products is carried out to determine and analyze efforts to increase sales of SME products, can provide convenience in the process of promotion and buying / selling carried out by SMEs to market products directly or through social media, especially in SMEs Lorong 310 Mariso Village Makassar City, and able to maximize the cost of selling their products. In determining the right sales strategy, there are many important factors to consider, such as the target market the first thing in determining the sales strategy is to know the target market of the product you offer, and the marketing system, as well as the type of product. Social media is a medium that customers often use to shop. Everyone has social media. Social media is great to use in improving sales strategies. Many customers will see your product with effective accuracy because all types of businesses carried out in this era of globalization all use the internet which can get a wider reach.